Hand Pruning and Training of Tropical and Subtropical Fruit Trees - Jeff Wasielewski; Jonathan Henry Crane; Carlos Balerdi (EDIS, 2020)
This new 6-page document explains the proper way to prune fruit trees using hand tools. An important aspect of growing tropical and subtropical fruit trees is size control through pruning. In addition to size control, pruning also makes it easier to spray the tree and harvest fruit from the tree. Pruning also makes the tree more hardy to wind events and healthier in general because you can remove damaged or unhealthy parts of the tree. Written by Jeff Wasielewski, Jonathan Crane, and Carlos Balerdi, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1372